The Role of Islamic Family Law in Realizing Gender Justice Through Law Number 13 of 2003 Concerning Employment in Indonesia - Dewi Afriani Faradilah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The issue of gender equality remains a relevant academic and social issue in legal development in Indonesia. The unequal roles between men and women in family life and the workplace demonstrate the need to integrate Islamic legal values into the national legal system. This study aims to analyze the role of Islamic family law in realizing gender justice and examine the application of Islamic family law principles to Law Number 13 of 2003 concerning Manpower. This study uses a literature study method with a juridical-normative approach to analyze legal norms in Islamic family law and Law Number 13 of 2003 concerning Manpower. This study found that Islamic family law plays a significant role in realizing gender justice through the principles of justice, balance, and responsibility between men and women. Islamic values affirm women as legal subjects with the right to education, employment, and self-protection proportionally according to their capacity. The relevance of Islamic family law to Law Number 13 of 2003 concerning Manpower is evident in the shared goal of ensuring the protection and welfare of women in the workplace. Ibn Taymiyyah's thoughts on wage justice align with legal provisions affirming the right to a living wage. Integrating Islamic legal values into the national employment system can strengthen equitable policies, address gender issues, and support women's participation in social and economic development.